Rancang Bangun Sistem Informasi Akademik Berbasis Website Dengan Metode SDLC - Wati Erawati; Sujiliani Heristian; Rachmat Adi Purnama (LPPM Universitas Bina Sarana Informatika, 2023)
In the conditions of today's globalization, information technology is developing rapidly. School really need an academic information system that supports and makes it easy for staff and parents of student.This research is motivated by a lack of information about children’s learning development. And because parents of schoolchildren lack information about their children's learning, the result is that parents do not know the development of their child’s school learning. The purpose of this research is of course to provide benefits for staff, teacher and parents to make it easier to get information or the results of school development from students. The method that the author uses in developing this software is the SDLC (Software Development Life Cycle) waterfall model. Therefore, researchers try to help with problems that exist in schools such as the lack of updating of data or information contained in schools. By creating a computerized system, it is hoped that it can work to help teacher provide information to parents of students. A web-based system that contains student attendance list, student daily activity plans, and report cards which are the end result of student development at school.The author tested this academic information system by using a regression test. The test results show that this system meets the test success criteria, such as acccuracy and speed in processing data. A website-based academic information system using the SDLC method can help users manage academic data easily, quicly and accurately. The SDLC method used can help develop a good and correct system, and according to user needs.